Wild edible plants in Ethiopia: a review on their potential to combat food insecurity - Lulekal, Ermias; Asfaw, Zemede; Kelbessa, Ensermu; Van Damme, Patrick (Afrika Focus, 2011)
This work reviews literature on ethnobotanical knowledge of wild edible plants and their potential role in combating food insecurity in Ethiopia. Information on a total of 413 wild edible plants belonging to 224 genera and 77 families was compiled in this review. Shrubs represented 31% of species followed by trees (30%), herbs (29%) and climbers (9%). Families Fabaceae (35 species), Tiliaceae (20) and Capparidaceae (19) were found to be represented by the highest number of edible species. About 56% (233) of species have edibility reports from more than one community in Ethiopia. Fruits were reported as the commonly utilized edible part in 51% of species. It was found that studies on wild edible plants of Ethiopia cover only about 5% of the country’s districts which indicates the need for more ethnobotanical research addressing all districts. Although there have been some attempts to conduct nutritional analyses of wild edible plants, available results were found to be insignificant when compared to the wild edible plant wealth of the country. Results also show that wild edible plants of Ethiopia are used as supplementary, seasonal or survival food sources in many cultural groups, and hence play a role in combating food insecurity. The presence of anthropogenic and environmental factors affecting the wild plant wealth of the country calls for immediate action so as to effectively document, produce a development plan and utilize the plants. Key words: ethnobotany, cultural diversity, food insecurity, indigenous knowledge, nutritional analysis